Pronomia persona dalam bahasa Jawa dialek Yogyakarta = The Personal Pronouns in The YogyakartaJavanese Dialect - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Every language or dialect has a personal pronoun system. The Yogyakarta Javanese sub dialect which is derived from the Surakarta Javanese dialect possesses its own system. A personal pronoun always appears in daily communication, thus its existence becomes very important. The personal pronouns in the Yogyakarta Javanese dialect have their peculiarity among the other Javanese dialect. This peculiarity is called an `a f3J dialect In this paper the writer pays attention to the dimension, the function and the typology of personal pronouns. A personal pronoun consists of two basic components, i.e. form and meaning. Morphologically, personal pronouns can be morphemes as well as words. As morphemes, personal pronouns can take the forms of basic morphemes, Le a prefix e.g. as a passive marker, a suffix, e.g. as a possessive can be monomorphemic and polymorphemic